Learning Tools for EFL Writing: What and How based on Upper Secondary School Students’ Perspectives - Evi Puspitasari; Elka Tsara (Universitas Hamzanwadi, 2022)
Writing in English is bit challenging since students should deal with not only organization and idea development but also the language. This study aims to explore the preferred learning tools used of upper secondary school students while writing and how the learning tools accommodate them in increasing the quality of their writing based upon their perspectives. This study belongs to descriptive qualitative research and took place at one of private upper secondary schools in Yogyakarta, Indonesia, with six students serving as research participants. A standardized open-ended interview and students’ writing works were used to acquire the data. The first finding revealed the learning tools opted by the students to support their writing are Youtube as a video sharing platform, Padlet as an online notice board, Grammarly, Google Translate, Grammar Checker as language support tools, and Google Docs and Microsoft Words for word processors. Meanwhile, from the two types of data, it is noticeable that students are helped by the tools. All of the aforementioned tools are able to linguistically and substantially improve their writing works by being language accommodation, idea development support, and writing organization assistance. Conclusion and recommendation are also discussed in this article after the findings and discussion are presented.